Grand (meta) challenges in planetary health: environmental, social, and cognitive - Butler, Colin David (Frontiers in Public Health, 2024)
The term “planetary health”, coined in the 1970s, arose from planetary consciousness, stimulated in part by the dawn of the space age, and commensurate recognition that our species faces extraordinary obstacles (“limits to growth”) if it is to fulfil its promise. While such awareness was then widely suppressed, awareness is reviving, driven by the now obvious perils, not only of climate change but also from weaponization and national aggression. Our neoliberal society (including in academic circles) has inappropriately rewarded articles and researchers that are biased toward optimism. This article proposes six grand (“meta”) challenges that planetary health must face.